Complicated pneumococcal pneumonia with pleural effusion or empyema in the 13‐valent pneumococcal conjugate vaccine era. Issue 5 (19th February 2019) - Díaz‐Conradi, Alvaro; Hernández, Sergi; García‐García, Juan José; Muñoz‐Almagro, Carmen; Moraga‐Llop, Fernando; Ciruela, Pilar; Izquierdo, Conchita; Campins, Magda; de Sevilla, Mariona F.; González‐Peris, Sebastià; Uriona, Sonia; Martínez‐Osorio, Johanna; et al.
Abstract: Aim: The aim was to analyze the epidemiological, microbiological and clinical characteristics of patients with complicated pneumococcal pneumonia with pleural effusion (PE) or empyema. Method: Prospective study in three Catalan hospitals in persons aged <18 years diagnosed with complicated pneumonia with PE or empyema with isolation of Streptococcus pneumoniae in blood or pleural fluid by culture or real‐time PCR between January 2012 and June 2016. Patients were divided into <2 years and 2‐17 years age groups. Epidemiological, microbiological, and clinical data of patients were compared annually in both groups. PCV13 vaccination coverage increased from 48.2% in 2012 to 74.5% in 2015. Results: We included 143 patients. The incidence of pneumococcal pneumonia was 6.83 cases × 10 −5 persons/year in cases with PE or empyema and 2.09 cases × 10 −5 person‐years in cases without (rate ratio [RR]: 3.27; 2.25‐4.86; P < 0.001). Empyema was more frequent than PE (79.7% vs 20.3%, P < 0.005). Of 143 cases studied, 93 (65.0%, P < 0.001) were diagnosed by real‐time‐PCR, 43 (30.1%) by culture and RT‐PCR and 7 (4.9%) by culture only. PCV13 serotypes were more frequent in complicated than in uncomplicated pneumonia (116/142, 81.7% vs 27/45, 60.0%; P = 0.003), especially serotype 1 (41/142, 28.9% vs 6/45, 13.3%, P : 0.036). From 2012 to 2015 there was a significant reduction in serotype 1 (16/43, 37.2% vs 3/27, 11.1%, P = 0.026), and a trend to an increase in non‐PCV13 serotypes (6/43, 14% vs 9/27, 33.3%, P = 0.054). Conclusions: A directly proportional relationship was observed between the reduction in pneumonia complicated with PE or empyema and a significant reduction in PCV13 serotypes, especially serotype 1, coinciding with increased PCV13 coverage.